Biographies of pregnancy and motherhood in adolescence within rural settlements in Rio Grande do Sul - Soares, Joannie dos Santos Fachinelli; Lopes, Marta Julia Marques (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to learn about and understand pregnancy and motherhood experiences in adolescence within rural settlements. The study started from a qualitative approach supported by the biographic method. Witnesses comprised women who experienced pregnancy and motherhood in adolescence. Data collection was performed in January and February 2009, by thematic biographic interview. The biographies show family trajectories of instability and constant moves as well as of precarious housing and employment. Pregnancy acceptance by the families of the adolescents is directly conditioned to the partner taking over the parenthood of the child and the adolescent mother as partner or spouse. The most frequently reported changes in the personal life deriving from pregnancy and motherhood were loss of freedom and increase of responsibility. At institutional level, it is observed the lack of public policies and, consequently, of services addressed to and adequate to health specificities within rural settlements.